The Implementation of the ARCS Learning Model to Improve Elementary School Students’ Learning Outcomes in Natural and Social Sciences - Arni Sasmitasari; Awaluddin Muin; Firdaus (PT. Lontara Digitech Indonesia, 2025)
This study aims to describe the implementation of the ARCS learning model in improving students’ IPAS learning outcomes among fifth-grade students at SD Inpres 12/79 Toro, Kecamatan Tanete Riattang, Kabupaten Bone. This research used Classroom Action Research, which was conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The subjects of this study were 29 fifth-grade students, consisting of 19 male students and 10 female students, and one fifth-grade teacher. Data were collected through observation and essay tests. The data were analyzed using descriptive qualitative analysis through data reduction, data description, and conclusion drawing. The results showed that the implementation of the ARCS learning model improved students’ IPAS learning outcomes. In Cycle I, 20 students, or 68.96%, achieved the minimum mastery criterion, with a mean score of 75.51. In Cycle II, the number increased to 25 students, or 86.20%, with a mean score of 80.31. The improvement also occurred in the learning process, where teacher and student activities became better after the reflection and improvement in Cycle II. These findings indicate that the ARCS learning model can create a more active, motivating, and meaningful learning process through the components of Attention, Relevance, Confidence, and Satisfaction. Therefore, the ARCS learning model can be used as an alternative strategy to improve students’ IPAS learning outcomes at the elementary school level.